Implanted microelectrode arrays for evaluating inhibited seizure modulated by light-responsive hydrogel. (9th September 2021) - Xie, Jingyu; Song, Yilin; Dai, Yuchuan; Xiao, Guihua; Yao, Qingxin; Xu, Shengwei; He, Enhui; Li, Xinrong; Lu, Zeying; Wang, Hao; Gao, Yuan; Fan, Zhongwei; et al.
Abstract: Microelectrode arrays (MEAs) are crucial tools for evaluating the modulating effects during in vivo neuromodualtion and it is crucial to develop novel strategies that allow for high spatiotemporal resolution, sustainable potential and dynamic monitoring during neurological disease therapy. Herein, we used a hydrogelator to assemble with ruthenium-based light-sensitive compound, RuBi-GABA, to prepare a light-responsive supramolecular hydrogel for suppressing seizures in the cortex of epileptic rats, which benefited the prolonged release of RuBi-GABA. Meanwhile, the real-time variations in neuronal action potentials (Spikes) and local field potentials (LFPs) during the modulation were recorded by nanomaterial-modified implanted MEAs. The results demonstrated the mean firing rate and LFP power sharply decreased 54.95% and 76.56% due to the light-activation of RuBi-GABA hydrogel in a timely manner. Additionally, the high synchronicity between pyramidal neurons and interneurons efficiently decreased after the illumination. Furthermore, simultaneous modulation of spikes and LFPs in time and frequency domain demonstrated that cortical seizures were efficiently inhibited from microscopic to mesoscopic signals. We anticipated that the strategy of using RuBi-GABA hydrogel for seizure control with the simultaneous effectiveness evaluation by the MEAs could lead to a novel approach for epilepsy therapy.